FROM SLAVERY TO BECOMING A LADY IN THE ABBASID ERA - Khulkar Ostanakulova (American Journals, 2023)
In this article, the wife and mother of the Abbasid caliphs, the person who manipulated the existing power economically, politically and religiously, using her feminine intelligence, the slave from captivity and later the beloved wife and mother of the caliph, Princess Khayzuran and her daughter-in-law, Princess Zubaidah, and another example that proved the importance of the queen’s role in this dynasty is the socio-economic and religious reforms of the mother of Caliph al-Muqtadir, Princess Shaghab.
Keywords: The Abbasid era, al-Mahdi, Khayzuran, al-Hadi, Harun al-Rashid, Zubaidah, al-Amin, al-Ma’mun, al-Mu’tadid, Shaghab, al-Muqtafiy, al-Muqtadir, al-Qahir.